Me and my AI: Exploring the effects of consumer self‐construal and AI‐based experience on avoiding similarity and willingness to pay - Loureiro, S. M. C.; Jiménez‐Barreto, J.; Bilro, R. G.; Romero, J. (Psychology and Marketing, 2024)
Artificial intelligence (AI) is reshaping consumer interaction with brands, but little is known about how brands can implement AI tools effectively. Drawing on consumer uniqueness and self‐construal theories, the authors examine the implementation of branded AI tools and their influence on consumers' experience, sense of uniqueness, and spending behavior. Across five studies, this research examines consumers' narratives about interacting with a branded AI tool (Study 1); tests the relationships between self‐construal, AI‐enabled consumer experiences, and avoidance of similarity (Studies 2A and 2B); evaluates in situ experience with a branded AI tool and its implications for spending behavior (Study 3); and delineates consumer preferences about the attributes of branded AI tools (Study 4). The findings reveal that individuals characterized by independent self‐construal are prone toward perceiving higher recognition and hedonic values during their experience with branded AI tools, partially enhancing consumer avoidance of similarity and influencing their willingness to pay for products that the AI tool recommends. For practitioners, the findings suggest developing a two‐fold value proposition strategy for consumers by generating personal and psychological value together with product and service recommendations.